STUDY OF COSMIC RADIATION NEAR THE EARTH'S NORTH GEOMAGNETIC POLE. - Pomerantz,Martin A. (1970)
Data were continuously recorded by the high counting rate neutron and meson detectors at Geopole Station, Thule, and were distributed to the World Data Centers. New equipment for providing punched paper tape output, and for monitoring neutron multiplicities, was constructed. Many facets of a wide variety of cosmic ray intensity variations have been studied, including the solar diurnal variations, north-south asymmetries, and solar particle precipitation. (Author) Various reprints included.